Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T14:54:41+02:00
A)
3x-1=5x
3x-5x=1
-2x=1
x=-½


b)
y-3=9-y
y+y=9+3
2y=12
y=6


c)
1/2z+6=z-1
½z-z=-1-6
-½z=-7
z=14


d)
-7b=7/8
b=-⅛
1 5 1
2010-04-15T14:55:15+02:00
A) 3x-1=5x
-2x=1 /:(-2)
x=-1/2

b) y-3=9-y
2y=12 /:2
y=

c) 1/2z+6=z-1
-1/2z=-7 /*(-2)
z=14

d) -7b=7/8 /*(-7)
b=6 1/8
  • vela
  • Początkujący
2010-04-15T14:57:48+02:00
3x-1=5x
5x=3x-1
5x-3x=-1
2x=-1 /:2
x= -1/2

y-3=9-y
y+y=9+3
2y=12 /:2
y=6

1/2z+6=z-1
z-1=1/2z + 6
z-1/2z=6+1
1/2z=7 / x2
z=14.